ANALISIS PENGARUH KOMPETENSI DAN PROMOSI TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA SEKRETARIAT DAERAH KABUPATEN BUNGO - Ansori Ansori; Hapzi Ali (Universitas Batanghari Jambi, 2015)
Applicability of Act No. 32 of 2004 on Regional Autonomy, which focuses on the district / city that gives broad authority, real and responsible to the area. The success of the implementation of regional autonomy is determined by the preparedness and ability of the region itself to manage and empower all potentials and resources available. In conjunction with the implementation of development in Bungo district, the civil servants in particular Bungo Bungo at the District Secretariat should also be able to improve the quality of work, in order to support the performance of the government to improve the quality of the extras in serving the community. Because employees are domiciled as an element of the State apparatus has a duty to provide services to the community in a professional, honest, fair and equitable in the administration of state duties, governance and development. In essence, civil servants is one of the main driving factors in the implementation of the development of both national and local levels.The purpose of this study alone, namely: 1) To determine the effect of competence on employee performance at the District Secretariat Bungo partially .; 2) To determine the effect of promotion to employee performance at the District Secretariat partially Bungo; and 3) To determine the effect of competence and promotion to employee performance at the District Secretariat Bungo simultaneously.This study used a descriptive method and quantitative analysis. The study population as many as 163 employees by the state in 2013, sampling technique in this research is based on a table Krejcie error of 5%, resulting in a study sample to 114 employees. Techniques of data collection using questionnaires. Technique using multiple linear regression analysis and testing continued with the R Square and partial hypothesis testing and simultaneous with the t test and F.Of multiple linear regression equations were conducted, the results of the study showed behold Competence (X1) and Promotion (X2) has an influence on employee performance. Where based on the results of t-test (partial) and F test (Simultaneous) showed behold Competence and promotion has a significant and positive effect on employee performance, where competence has a greater influence than the promotion in order to improve employee performance. This explains behold if the employee has a good competence in carrying out his job, and supported by the implementation of the promotion, it will be able to improve employee morale, thereby increasing the performance of the employees themselves in carrying out its duties and functions substantially.Keywords: Competence, Promotion and Employee Performance.